2022
DOI: 10.3390/ijms231911513
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine and Rutaecarpine as Potential Anticancer Compounds: A Combined Computational Study

Abstract: Evodiamine (EVO) and rutaecarpine (RUT) are the main active compounds of the traditional Chinese medicinal herb Evodia rutaecarpa. Here, we fully optimized the molecular geometries of EVO and RUT at the B3LYP/6-311++G (d, p) level of density functional theory. The natural population analysis (NPA) charges, frontier molecular orbitals, molecular electrostatic potentials, and the chemical reactivity descriptors for EVO and RUT were also investigated. Furthermore, molecular docking, molecular dynamics simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
(61 reference statements)
2
1
0
Order By: Relevance
“…As shown in Figure 3 , we plotted the binding models of EVO-1 and EVO-6 with TOP1. The binding conformations of EVO-1 and EVO-6 with TOP1 were very similar, which is consistent with the previous predicted binding mode of EVO with TOP1 ( Liu et al, 2022 ). Despite the nonplanar structure of EVO and its derivatives, they can still bind to the active site of TOP1.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure 3 , we plotted the binding models of EVO-1 and EVO-6 with TOP1. The binding conformations of EVO-1 and EVO-6 with TOP1 were very similar, which is consistent with the previous predicted binding mode of EVO with TOP1 ( Liu et al, 2022 ). Despite the nonplanar structure of EVO and its derivatives, they can still bind to the active site of TOP1.…”
Section: Resultssupporting
confidence: 90%
“…For compound EVO-4, the optimized structure was consistent with the X-ray structure (Nie et al, 2020). The optimized geometries of other derivatives were almost nonplanar, similar to the optimized geometry of EVO (Liu et al, 2022).…”
Section: Dft Calculation Studiessupporting
confidence: 67%
“…It is basically an indolequinone alkaloid extracted from Evodia rutaecarpa , a multi-purpose herb native to China. 22 The mechanism of action of EVO includes the activation of caspases, which are critical enzymes responsible for executing apoptosis. 22 However, despite its potent anticancer efficacy, the clinical application of EVO is hindered by its limited pharmacokinetics, including poor aqueous solubility, diminished gastrointestinal absorption, and reduced oral bioavailability.…”
Section: Limitations Of Conventional Therapiesmentioning
confidence: 99%
“… 22 The mechanism of action of EVO includes the activation of caspases, which are critical enzymes responsible for executing apoptosis. 22 However, despite its potent anticancer efficacy, the clinical application of EVO is hindered by its limited pharmacokinetics, including poor aqueous solubility, diminished gastrointestinal absorption, and reduced oral bioavailability. 22 Additionally, EVO administration is associated with adverse effects ranging from gastrointestinal disturbances (diarrhoea, constipation, anorexia, and stomach discomfort) to severe toxicities (hepatotoxicity and cardiotoxicity) under high doses or prolonged usage.…”
Section: Limitations Of Conventional Therapiesmentioning
confidence: 99%
“…It is now well established that theoretical methods are an efficient multipurpose tool for chemistry, biochemistry, and material science. Recent scientific efforts have shown that they can help us understand various phenomena, for example, reaction mechanisms or reactivity [ 35 , 36 , 37 , 38 ], electron density distribution [ 39 , 40 , 41 ], and elusive structure of complex biochemical systems or radical centers [ 42 , 43 , 44 ], anticancer [ 35 , 45 ] and antioxidant properties [ 46 , 47 , 48 , 49 , 50 , 51 ], soot formation [ 52 ] or pesticide decomposition [ 53 ]. The exchange coupling between paramagnetic centers has been a subject of such investigations at the density functional theory (DFT) and ab initio levels, but these studies were mainly limited to the interaction between metallic centers [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%